Characterization of a novel passive personal fast neutron dosimeter based on a CR-39 track detector in monochromatic neutron fields via Monte Carlo simulations and experiments. (August 2021) - Bolzonella, M.; Caresana, M.; Ferrarini, M.; Babut, R.
Abstract: The response in terms of personal dose equivalent of a passive fast neutron dosimeter composed of a CR-39 detector coupled with a 1 -cm-thick PMMA radiator is investigated in monochromatic neutron fields via simulations and experiments. In particular, the simulations were performed through the Monte Carlo FLUKA code (version 2011.2x.5), while the experimental fields were produced at the AMANDE facility ( IRSN, France). The dosimeter response is studied with respect to both the energy and the angle of incidence of the radiation field on the device. The simulated response shows a quite stationary trend, that is, minimal variation across a wide energy range, also for different irradiation angles. The agreement between simulated and experimental responses indicates the simple and cheap dosimeter presented as promising for personal dosimetry applications in practical situations. Highlights: Characterization of the dosimeter response in terms of personal dose equivalent H p ( 10 ) . Investigation of the angular dependence of the response. Response function in terms of personal dose equivalent is obtained in an extended energy range ( 100 keV ÷ 1 GeV ).